Kinetic investigations of chlorine atom initiated photo oxidation reactions of 2, 3-dimethyl-1, 3-butadiene in the gas phase: an experimental and theoretical study. Issue 72 (18th July 2016) - Vijayakumar, S.; Rajakumar, B.
Abstract : Rate coefficients for the reaction of chlorine atoms with 2, 3-dimethyl-1, 3-butadiene were measured over the temperature range of 269–393 K by using a relative rate experimental method with reference to isoprene and 1-pentene. Abstract : Rate coefficients for the reaction of chlorine atoms with 2, 3-dimethyl-1, 3-butadiene were measured over the temperature range of 269–393 K by using a relative rate experimental method with reference to isoprene and 1-pentene. Concentrations of the 2, 3-dimethyl-1, 3-butadiene and reference compounds were monitored by gas chromatography equipped with a Flame Ionization Detector (FID). The obtained rate coefficient for the reaction of 2, 3-dimethyl-1, 3-butadiene with Cl atoms at 298 K is k = (4.48 ± 0.46) × 10 −10 cm 3 per molecule per s, which is in good agreement with the reported rate coefficient at 298 K and 760 Torr. The obtained temperature dependent rate coefficient is k 2, 3-dimethyl-1, 3-butadiene+Cl (269–363 K) = (4.59 ± 0.67) × 10 −11  exp[(663.13 ± 45.8)/ T ] cm 3 per molecule per s. To further understand the reaction mechanism of butadienes with Cl atoms, theoretical calculations were performed for the reactions of 2-methyl-1, 3-butadiene (isoprene) and 2, 3-dimethyl-1, 3-butadiene with Cl atoms as a function of temperature using Conventional Transition State Theory (CTST) in combination with QCISD( T ), CCSD( T ) and MP2 levels of theory with different basis sets. The theoretically calculated temperature dependent rate coefficient is k 2, 3-dimethyl-1, 3-butadiene+Cl (200–400 K) = (4.12 ± 0.38) × 10 −12  exp[(1419.2 ± 26)/ T ] cm 3 per molecule per s which is in excellent agreement with our experimentally measured rate coefficients. The rate coefficient was observed to be increasing with the substitution of hydrogen atoms by methyl groups.